2020
DOI: 10.1101/2020.04.15.20066183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of early scientific literature in response to COVID-19: a scientometric perspective

Abstract: Background. In the early phases of a new pandemic, identifying the most relevant evidence and quantifying which studies are shared the most can help researchers and policy makers. The aim of this study is to describe and quantify the impact of early scientific production in response to COVID-19 pandemic.Methods. The study consisted of: 1) review of the scientific literature produced in the first 30 days since the first COVID-19 paper was published; 2) analysis of papers' metrics with the construction of a "Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Some other relevant bibliometric studies (Chahrour et al, 2020; Chen et al, 2020; DE Felice & Polimeni, 2020; Golinelli et al, 2020; Hamidah et al, 2020; Hossain, 2020; Zhai et al, 2020; Zhou & Chen, 2020) analyzed the similar indices, such as authors, countries, languages, citations, institutions, sources, and types. These studies are affected by at least two problems.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other relevant bibliometric studies (Chahrour et al, 2020; Chen et al, 2020; DE Felice & Polimeni, 2020; Golinelli et al, 2020; Hamidah et al, 2020; Hossain, 2020; Zhai et al, 2020; Zhou & Chen, 2020) analyzed the similar indices, such as authors, countries, languages, citations, institutions, sources, and types. These studies are affected by at least two problems.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, several COVID-19-related bibliometric papers added some relevant findings to the international scholarships. While some researches took only the recent publications into account (Golinelli et al, 2020; Lou et al, 2020; Zhai et al, 2020), some researches analyzed publications from a relatively longer span (Tao et al, 2020; Zhou & Chen, 2020). Identifying some knowledge-gaps in the previous literature, this bibliometric analysis presents some novel findings.…”
Section: Introductionmentioning
confidence: 99%
“…On December 31, 2019 an official case of a novel respiratory disease of the category of coronaviruses, named Covid-19, was reported in Wuhan, China, marking the beginning of what proved to be one of the direst and most devastating viral outbreaks in the modern history (Sohrabi et al 2020 ; Wang et al 2020 ). This was immediately followed by an unprecedented and swift response of the academic community to address various dimensions of this health crisis and prompted an avalanche of scholarly publications on this topic (Golinelli et al 2020 ; Haghani et al 2020 ; Kagan et al 2020 ). In less than five months, more than 12,000 publications on this topic have already been indexed by Scopus with the number increasing figuratively every day in considerable increments 1 (Torres-Salinas et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The retrieved documents on bibliometrics studies about SARS-CoV-2 showed a significant variation in their results, ranging from 153 to 21,395 articles with an average of 4,279 (± 5,510), although it was possible to observe some similarities. Golinelli 35 and Gori, Boetto and Fantini 34 , aimed to measure what had been published in the first 30 days of the epidemic outbreak. Both studies used the PubMed platform and the same keywords combination as search terms, obtaining very similar results: 239 and 234 retrieved articles, respectively.…”
Section: Resultsmentioning
confidence: 99%